2016
DOI: 10.1590/0104-6632.20160333s20150056
|View full text |Cite
|
Sign up to set email alerts
|

OXIDATIVE-REFORMING OF METHANE AND PARTIAL OXIDATION OF METHANE REACTIONS OVER NiO/PrO2/ZrO2 CATALYSTS: EFFECT OF NICKEL CONTENT

Abstract: -In this work the behavior of NiO-PrO2-ZrO2 catalysts containing various nickel loadings was evaluated in the partial oxidation of methane and oxidative-reforming reactions of methane. The catalysts were characterized by X-Ray Diffraction Analysis (in situ-XRD), Temperature Programmed Reduction (H2-TPR), Scanning Electron Microscopy (SEM/EDX) and Adsorption-Desorption of nitrogen (BET area). The reactions were carried out at 750 °C and 1 atm for 5 hours. The catalysts were studied with different nickel content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The size of ZrO2 primary crystallites (calculated from the Scherrer equation using the 2θ diffraction peak at 31°), was 11 nm for the Zr-containing materials. This is in agreement with the study of Asencios et al [19], where ZrO2 crystallites with non-variable size were detected by XRD. Moreover, the calculated mean Ni crystallite size (at 2θ ca.…”
Section: Tpd-co2 Results Are Presented Insupporting
confidence: 94%
See 1 more Smart Citation
“…The size of ZrO2 primary crystallites (calculated from the Scherrer equation using the 2θ diffraction peak at 31°), was 11 nm for the Zr-containing materials. This is in agreement with the study of Asencios et al [19], where ZrO2 crystallites with non-variable size were detected by XRD. Moreover, the calculated mean Ni crystallite size (at 2θ ca.…”
Section: Tpd-co2 Results Are Presented Insupporting
confidence: 94%
“…Y 3+ [9,17,18]. This results in the formation of defects in the crystal structure of zirconia, together with oxygen vacancies in its oxygen sub-lattice, which are known as beneficial in the minimization of carbon deposits [9,[19][20][21]. The ZrO2-Y2O3 solid solution was studied in the past in different reforming processes [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The result suggested that PrO2 contributed to the formation of Ni 0 active phases due to high metal dispersion and metal-support interaction in contrast [74].…”
Section: Nickel Catalystsmentioning
confidence: 99%
“…In this sense, it has been reported that by changing the molar relation of reactants in the ORM, the H 2 /CO ratio in the obtained syngas could be controlled for further synthetic (5 purposes. 46 Indeed, the possibility of increasing the H 2 /CO ratio of the syngas has been reported by changing the O 2 /CH 4 ratio in the process. This approach is based on the contribution of the two reactions involved in the ORM process; the partial oxidation of methane and the dry reforming of methane (Equations 5 and 6).…”
Section: Co 2 and O 2 Stability Permeation Testmentioning
confidence: 99%